Genome Analysis Coupled With Transcriptomics Reveals the Reduced Fitness of a Hot Spring Cyanobacterium Mastigocladus laminosus UU774 Under Exogenous Nitrogen Supplement - Mukherjee, Mayuri; Geeta, Aribam; Ghosh, Samrat; Prusty, Asharani; Dutta, Subhajeet; Sarangi, Aditya Narayan; Behera, Smrutisanjita; Adhikary, Siba Prasad; Tripathy, Sucheta (Frontiers in Microbiology, 2022)
The present study focuses on the stress response in a filamentous, AT rich, heterocystous cyanobacterium Mastigocladus laminosus UU774, isolated from hot-spring, Taptapani located in Eastern part of India. The genome of UU774 contains an indispensable fragment, scaffold_38 of unknown origin that is implicated during severe nitrogen and nutrition stress. Prolonged exposure to nitrogen compounds during starvation has profound adverse effects in UU774 leading to loss of mobility, loss of ability to fight pathogens, reduced cell division, decreased nitrogen fixing ability, reduced ability to form biofilms, reduced photosynthetic and light sensing ability, reduced production of secreted effectors and chromosomal toxin genes just to name a few. Among the genes showing extreme down regulation when grown in media supplemented with nitrogen with fold change > 5 are transcriptional regulator gene WalR, carbonic anhydrases, RNA Polymerase Sigma F factor, fimbrial protein, twitching mobility protein. The reduced expression of key enzymes involved in uptake of phosphate and enzymes protecting oxygen sensitive nitrogenase are significant during presence of nitrogen. UU774 presumably withstands heat by over expressing peptidases that may be degrading abnormally folded proteins produced during heat. Absence of a key gene responsible for the heterocyst pattern formation, patS and an aberrant hetN without functional motif probably leads to the formation of chaotic heterocyst pattern in UU774. We suggest that UU774 has diverged from Fischerella sp. PCC 9339, another hotspring species isolated from the USA.